Penerapan Location Based Service(LBS) Pada Sistem Pencarian Kontrakan Dengan Metode Prototype - Dicky Hermawan; Wiyanto Wiyanto; Tri Ngudi Wiyatno (LPPM, 2023)
The lack of information about rentals such as descriptions and prices make it difficult for seekers to determine which rental option is in accordance with their wishes and also the price. With the conventional search process, rent seekers inevitably take the time and energy to find rentals according to their wishes, location and of course the price. This study aims to apply the location base service to support the search for rentals that make it easy and according to the wishes of rented seekers in Bekasi Regency as well as a promotional media for rented business owners for household needs, using the main method, namely location base service to solve the problem of finding a rental business that is still ongoing. many shortcomings and the prototype method as a system development method that supports this research. The result of this research is that the koskuappfront application is able to make renting search more efficient in terms of time and cost, as well as collecting rental information in one container that provides rental information.